1985
DOI: 10.1021/bi00322a007
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of respiratory nitrate reductase from Escherichia coli K12

Abstract: Purified respiratory nitrate reductase from Escherichia coli is able to use either reduced viologen dyes or quinols as the electron donor and nitrate, chlorate, or bromate as the electron acceptor. When reduced viologen dyes act as the electron donor, the enzyme follows a compulsory-order, "Theorell-Chance" mechanism, in which it is an enzyme-nitrate complex that is reduced rather than the free enzyme. In contrast, if quinols are used as the electron donor, then the enzyme operates by a two-site, enzyme-substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
104
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 32 publications
7
104
1
Order By: Relevance
“…The NarI mutant membranes were also assayed for the NO 3 Ϫ -dependent reoxidation of reduced benzyl viologen (BV . ϩ ) for which NarI is not required (2,24). Wild-type NarGHI has a specific activity of 100 mol of nitrate reduced min Ϫ1 (mg of NarGH) Ϫ1 (Table II).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The NarI mutant membranes were also assayed for the NO 3 Ϫ -dependent reoxidation of reduced benzyl viologen (BV . ϩ ) for which NarI is not required (2,24). Wild-type NarGHI has a specific activity of 100 mol of nitrate reduced min Ϫ1 (mg of NarGH) Ϫ1 (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the BV . ϩ :NO 3 Ϫ oxidoreductase activity appears to be independent of the presence of NarI (2,24). This prompted us to investigate whether the NarI-H56R mutation has any effect on the assembly or conformation of the NarH [Fe-S] clusters.…”
Section: Fig 3 Redox Titration Of Narghi-enriched Membranesmentioning
confidence: 99%
See 3 more Smart Citations